THE EFFECT OF USING MULTIPLICATION BAG PROTOTYPES ON THE UNDERSTANDING OF MULTIPLICATION CONCEPTS IN GRADE 2 STUDENTS OF SDN SILIH ASUH III CIREBON CITY - Nuryenda, Endang Yuda; Roheni; Syahfitri, Gita Asri (Jurnal Ilmu Pendidikan Dasar (JIPDA), 2024)
This study aims to determine how the use of multiplication bag props in multiplication material on the understanding of the concept of multiplication in class II SDN Silih Asuh III Cirebon City, to determine how the effect of the use of multiplication bag props on the understanding of the concept of multiplication in class II SDN Silih Asuh III Cirebon City and to find out how much influence the use of multiplication bag props has on the understanding of the concept of class II SDN Silih Asuh III Cirebon City. Through a quantitative approach, this study used a one group pretest-posttest design method. The sample in the study consisted of one class of 20 students who were tested before and after the use of the multiplication bag props. Data were collected through written tests administered in three stages, namely pretest, treatment and posttest. Data analysis showed that there was an increase in the understanding of the concept of multiplication after treatment using the multiplication bag props, with an average pretest score of 56.9 and an average posttest score of 87. From the results of the t test conducted, a significance value of 0.000 was obtained. Since the significance value is <0.05, Ho is rejected and Ha is accepted, indicating a significant increase in students' understanding of the concept of multiplication, confirming that teaching aids can function as effective media in learning. The findings provide insights for educators to develop teaching methods that are more effective in teaching multiplication concepts.